Psychometric testing of a person-centred care scale the Eden Warmth Survey in a long-term care home in New Zealand - Yeung, Polly; Rodgers, V.; Dale, M.; Spence, S.; Ros, B.; Howard, J.; O'Donoghue, K. (eContent Management, 2016)
Background: Traditional nursing homes have been viewed as dominated by the medical model. Since the 1990s, the Eden AlternativeTM has become a significant model in systemic transformations in nursing homes. The purpose of this study was to evaluate the psychometric performance of the 20 items of the Eden Warmth Survey – Residents (EWS-R) in an aged-care home. Design: A resident's satisfaction survey was used to collect a sample of 85 long-term care home residents. Methods: Psychometric evaluation included item analyses, reliability including internal consistency and stability, criterion-related validity and construct validity. Results: The reduced 13 items demonstrated adequate reliability (a = 0.82) with two factors, Trust and Connectedness with Others and Care Practices, extracted and contributed to 57.9% of the total variance. Conclusions: The 13-item of EWS-R can be considered as a reliable and predictive scale for assessing quality of life and overall satisfaction on people living in long-term care facilities.